Perancangan Modul Persetujuan Otomatis dan Klasifikasi pada Sistem Persetujuan Lapor Diri Pensiun Menggunakan FSA - Harianto; Windu Gata; Virda Mega Ayu; Achmad Bayhaqy (KITA Institute, 2023)
Retired Dana Pensiun Perkebunan Defined Benefit Pension Plan (PPMP) participants are required to certify annually that they still meet the criteria for being a valid pensioner. The retiree uses the Dapenbun online application to take a photo of himself and her ID card and wait for the data to be processed by the administrator. Pensioners who do not report will have their pension entitlements suspended. The number of retirees managed by the Plantation Pension Fund is over 216,000, and managers are overwhelmed with approval at the start of the re-data period. For this reason, authors design systems that can run automated approval and classification systems to facilitate data approval. Applying the FSA concept to this system reduces the processing of participant data as automation is applied to the first process of automatic termination of pensions for children aged 21 and over, second data with criteria for automatic approval. It will be faster. Categorizing data reduces approval errors and makes it easier for users to approve data.